EMBRYONIC CELL ADHESIVENESS: DO SPECIES DIFFERENCES EXIST AMONG WARM-BLOODED VERTEBRATES? - Burdick, Morton L. (1969)
Mouse and chick embryonic myocardial cells sort out from each other in aggregates of heart ventricle cells. This result invalidates the generalization that embryonic cells of a given tissue from different warm-blooded vertebrate species possess identical cell-sorting properties.